Modelling and Analysis of a Power Transformer Using Finite Element Analysis - Muhammad, Sabo Sani; Abdulrazak, Sabo; Bakare, G. A.; Abdulhafiz, Sabo; Nazif, D. M. (Darul Yasin Al Sys, 2025)
This study presents an enhanced Finite Element Method (FEM) model for comprehensive analysis of power transformers, addressing electromagnetic, thermal, and electrostatic performance aspects with improved accuracy and efficiency. Conventional analytical approaches to evaluating transformer characteristics—such as core losses, copper losses, magnetic flux distribution, and thermal behavior—are often labor-intensive and susceptible to inaccuracies. To overcome these limitations, a double discretization FEM (DD-FEM) framework was developed using ANSYS Maxwell and ANSYS Mechanical software to simulate a 30 MVA, 132/33 kV three-phase power transformer. The electromagnetic simulation yielded core and copper losses of 19.62 kW and 97.03 kW, respectively, with DD-FEM reducing absolute errors by 1.38% and 1.48% compared to standard FEM methods. Thermal modeling under normal loading conditions indicated a peak winding temperature of 94.2°C, rising to 112.9°C during overloading (33 MVA), thus justifying the need for forced cooling systems. Electrostatic analysis confirmed that electric field stresses between windings remained within safe operational limits (10.48 kV/mm²), though a localized insulation weakness was identified between the low-voltage winding and the core (3.74 kV/mm²). Across all evaluated parameters, the DD-FEM model showed superior alignment with benchmark analytical results, reducing relative errors in core loss estimation by up to 12.2%. These results affirm the efficacy of the enhanced FEM approach in optimizing transformer design, enhancing operational reliability, and reducing engineering uncertainty, particularly under varying load and fault scenarios. The study demonstrates the critical role of advanced numerical tools in modern transformer engineering and high-fidelity system simulation.